2011
DOI: 10.1007/s00330-011-2287-z
|View full text |Cite
|
Sign up to set email alerts
|

The vestibulocochlear nerve: aplasia and hypoplasia in combination with inner ear malformations

Abstract: Vestibulocochlear nerve deficiency can be strongly suspected in certain inner ear malformations • Bony cochlear aplasia and cochlear nerve aplasia are strongly correlated • In semicircular canal aplasia, hypoplasia of the vestibular nerve can be found • Before cochlear implantation, the type of any IEM should be fully understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 13 publications
1
17
0
2
Order By: Relevance
“…In accordance with Giesemann et al [29] the present study found that IP-I malformations can be associated with hypoplastic/aplastic cochlear nerves. Hence, the diameter of the cochlear nerve was normal in all patients with IP-II and IP-III malformations in this study.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with Giesemann et al [29] the present study found that IP-I malformations can be associated with hypoplastic/aplastic cochlear nerves. Hence, the diameter of the cochlear nerve was normal in all patients with IP-II and IP-III malformations in this study.…”
Section: Discussionsupporting
confidence: 93%
“…Although it is best to perform both CT and MRI for cochlear implant candidates, in special situations in which there are financial constraints, CT should be performed and MRI done selectively in cases where cochlear nerve deficiency is suspected. Previous studies [Casselman et al, 1997;Giesemann et al, 2012] and this study show that CVM may be accompanied by cochlear nerve deficiency, suggesting that MRI should be done to assess cochlear nerve deficiency in candidates for cochlear implantation who have CVM. We found a high incidence of cochlear nerve deficiency in children with CVM type C or type D, so our data suggest that MRI should be considered essential for patients who have CVM type C or type D on TBCT.…”
Section: Discussionmentioning
confidence: 99%
“…MRI is the choice of imaging modality to identify the status of the cochlear nerve [Casselman et al, 1997;Glastonbury et al, 2002], but MRI cannot depict the detailed mastoid anatomy as well as CT can, because of the limitation of its resolution. Furthermore, the incidence of cochlear nerve deficiency is very low in children with normal inner ear morphology [Miyasaka et al, 2010;Giesemann et al, 2012] so it is not cost-effective to undertake MRI for all cochlear implant candidates. Although it is best to perform both CT and MRI for cochlear implant candidates, in special situations in which there are financial constraints, CT should be performed and MRI done selectively in cases where cochlear nerve deficiency is suspected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoplasia and aplasia of the vestibulocochlear nerve (VCN) is most often found in combination with certain inner ear malformations, but can also occur separately with a morphologically intact inner ear as viewed on CT scans [8]. In 1997, Casselman et al [2] classified VCN aplasia and hypoplasia as follows: type 1 as an aplasia of the VCN associated with stenosis of the internal auditory canal; type 2a as an existing common VCN with aplasia or hypoplasia of its cochlear branch and with labyrinthine malformation present; and type 2b in combination with a normal labyrinth.…”
Section: Hypoplasia and Aplasia Of The Vestibulocochlear Nerve (Vcn)mentioning
confidence: 99%